PENGARUH FERMENTASI RAGI TERHADAP VOLUME BIOALKOHOL FERMENTASI KULIT PISANG BARANGAN (MUSA PARADISIACA) - Halisah Suriani; Habibul Akram (KOLONI, 2022)
This study aims to determine the effect of yeast concentration on the volume of bioalcohol of Barangan banana peel (Musa paradisiaca) on the right amount of yeast. This research was conducted at the Laboratory of the Faculty of Teacher Training and Education at Gunung Leuser (FKIP - UGL) Kutacane on 15-22 November 2021. The design used in this study was a Completely Randomized Design (CRD) with 5 (five) treatments and 3 (three) treatments. replications, so a total of 15 trials. The parameter observed was the volume of bioalcohol in liquid form, the metabolite of Barangan banana peel (Musa paradisiaca) after being fermented with yeast. The results showed that there was a significant effect on the volume of bioalcohol produced, this can be seen through the results of data analysis (CRD) which is very influential where F count > F table then Ho is rejected and Ha is accepted. The results of data analysis of the effect of yeast concentration on the volume of bioalcohol fermented banana peels (Musa paradisiaca) had a significant effect. This is evidenced by the calculated F value (5.27) > F table (3.48). Thus, Ha is accepted. Keywords:  yeast concentration, volume of bioalcohol, banana peels